READING AS ONE OF THE MAIN SKILLS IN TEACHING ENGLISH - Arzieva, B.A.; Tajetdinova, A. (FAN va JAMIYAT, 2016)
The article deals with the study of one of the important language skills as reading in teaching English. The author also studies various kinds of reading-reading aloud and silent reading and different methods of teaching reading. Reading is very important for the development of such language skills as speaking and writing.